Application of spiroergometry to determine work metabolism related strain in the course of cable work with a mini forestry crawler. Issue 2 (3rd May 2020) - Berendt, Ferréol; Hoffmann, Stephan; Jaeger, Dirk; Prettin, Stephan; Schweier, Janine
ABSTRACT: Winching is a common practice for extracting logs in forest operations; however, it requires significant physical effort by humans to pull-out the cable to the felling site. The aim of this study was to quantify the intensity of this activity by measuring human effort parameters during different winching operations under experimental conditions with a mini forestry crawler. Internal energy provision was determined by a portable spiroergometric device which was linked to beat-to-beat heart rate measurement. These data as well as the pulling force were assigned to the respective distance markers. After a small decrease over the first few meters, the pulling force increased as the pull-out distance increased. A maximum heart rate reserve of 67.3% and a metabolic equivalent (MET) of 11.6 were reached at the choking point in the flat winching direction. When winching was simulated uphill, peak values between 6.6 and 9.1 METs were reached at the end of the winching process. Winching with a remote-controlled mini forestry crawler over a distance of 50 m was rated as vigorous work, since METs of 6.0 for the entire work cycle were frequently exceeded. Thus, winching distances should be kept shorter in order to reduce metabolic strain. Moreover, winching teams should take active breaks and rotate work tasks during the working day to enable the necessary recovery.